Implementation Of The Sharia Productive Financing Program To Increase Income At The Pujon Syariah Madani National Capital - Alwi Abdul Aziz; Fani Firmansyah (International Journal of Economics, Commerce, and Management, 2024)
The aim of carrying out this research is to find out the implementation of the Sharia productive financing program in increasing income at PT Pemodalan Nasional Madani Syariah Pujon. The type of research used in this research is field research (Field Research). This research approach is descriptive analysis. This research aims to determine the impact of the Sharia productive financing program on increasing the income of women's MSMEs in Pujon. In preparing this research, the author clarified the data sources into 2 types, namely: 1) Primary data; 2) Secondary Data. Data collection techniques in this research were obtained through the following methods and stages: 1) interviews; 2) Observation and 3) documentation. The results of this research are the productive financing application mechanism at PT Permodalan Nasional Madani, namely that prospective customers submit applications by bringing initial documents and filling in the financing application form. Customers who take out or carry out productive financing with PT Permodalan Nasional Madani as a business need, the micro-business runs by the customer experiences an increase in income. So that with this financing, the business run by the customer can develop and increase the customer's income. By increasing the stock of goods or equipment in the business run by the customer, the business also experiences progress in terms of income, production and performance